A Systematic Review on Various Therapeutic Options for Coronavirus Outbreak - Khan, Sharib Raza; Sharma, Babita; Bhattacharya, Sankha (Journal of Drug Delivery and Therapeutics, 2021)
SARS-CoV-2 (Severe Acute Respiratory Syndrome Coronavirus-2) or coronavirus disease that emerged in Wuhan, China’s Hubei province. According to a Wuhan citizen, the virus spread from the Wuhan fish market to humans via a form of waterborne transmission. The WHO proclaimed the SARS-CoV-2 Pandemic a global public health emergency in March of the following year. Rather than influencing the individual animals mostly, the movement of humans and a few days later, the infection spread to other parts of the world by the distribution of specimens to animals and by the movement of humans, causing considerable illness in human populations. An estimated one and a total of nearly sixty-eight million two hundred and fifty-six million people have been impacted, including one and a million thousand five hundred and sixty thousand fatalities in more than two hundred countries around the world. As of the present, there are no medicines or vaccinations against the world’s first SARS-CoV-2 virus are in clinical trials molecular and cellular studies of CoVs, as well as their care, were reviewed in this latest assessment. Keywords: SARS-CoV-2, WHO, Global pandemic, Human coronaviruses, Pathogenesis, Treatments